A comparative study of various detection methods to assess seed borne mycoflora in different linseed genotypes: A comparative study of various detection methods to assess seed borne mycoflora in different linseed genotypes - POONAM SINGH PARTE; ASHULATA KAUSHAL; TARUN PRADHAN; SATISH KAUSHAL (Journal of Oilseeds Research, 2023)
A total of 11 associated mycoflora were detected by various incubation methods i.e., Aspergillus niger, Aspergillus flavus, Aspergillus fumigatus,Fusarium spp., Alternaria spp., Colletotrichum spp. Rhizopus spp., Penicillium spp., Trichoderma spp., Cladosporium spp., and Curvularia spp. Agar plate method gave the highest frequency of associated mycoflora. Linseed genotype SLS -93 showed highest frequency of associated mycoflora with minimum germination percentage.